Patient-reported outcome survey post primary cleft lip and palate surgery in Hospital Kuala Lumpur using oral health impact profile (COHIP) questionnaire - Abas, Muhammad Firdaus (2015)
Introduction: Patient-reported outcome survey is one of the modality to assess the outcome of surgical intervention from patient’s perspective. Cleft lip and palate is one of the most common congenital abnormality encountered in plastic surgery field. The primary surgical repair for both cleft lip and palate were among the commonest procedure done in treating cleft lip and palate patients. The outcome of the surgery includes the aesthetic results, speech, functionality self image and quality of life. Child Oral Health Impact Profile questionnaire is one of the reliable and valid assessment tools in the form of questionnaire to evaluate patient’s reported outcome post primary cleft lip and palate surgery. Objectives: The aims of this study is to evaluate the patients reported outcome post primary cleft lip and palate surgery in Hospital Kuala Lumpur using Child Oral Health Impact Profile (COHIP) questionnaire. Specifically is to describe patient’s perspective regarding their oral health, functional well-being, social/emotional wellbeing, school environment and self image post cleft lip and palate repair using the COHIP score. Second specific objective is to compare the mean difference of COHIP score between early and late timing of surgery. Third specific objective is to compare mean difference of COHIP score between 3 categories of surgeons. Methodology: A cross-sectional study was carried out on patients with cleft lip and palate in Hospital Kuala Lumpur, Malaysia. All patients details with orofacial cleft operated between 1999 and 2005 that have been treated at the Department of Plastic and Reconstructive Surgery, Hospital Kuala Lumpur, Malaysia were retrieved from the operation theatre logbook to see the eligible patients in the age group of 8 to 14 years old to participate in the study. From the details collected, the patients that fulfilled the criteria were invited to participate in the study via a phone call. The appointment date was given to the patients. On the day of the appointment the patients and their parents/guardians were given a participant information sheet, contains the details of the study conducted. The researcher provided information and answered any question regarding the study. The consent form for parents/guardians and the child participant assent form were distributed after both parents/guardians and the patients agree to participate in the study. The COHIP Questionnaire was distributed to the participant after the researcher wrote down all the demographic details. The patient was given 30 minutes to complete the questionnaire. Results: A total of 82 patients participated in the study. Of these, 41 (50.0%) were male and 41 (50.0%) were female with 1:1 ratio of male to female. Their age range is between 8 years old to 14 years old, with a mean age of 11.3 years old. The majority of the subjects had left unilateral cleft lip and palate n=44 (53.7%). About one-third of the subjects had bilateral cleft lip and palate n=25 (30.5%) and the remainder had right unilateral cleft lip and palate n=13 (15.9%). Majority of the subjects were operated by the specialist n=39 (47.6%), whereby consultants operatedon 35 subjects (42.7%) and trainee operated on 8 subjects (9.8%). Early primary cleft palate repair less than 1 year old of age were done to 52 subjects (63.4%). Late primary cleft palate repair more than 1 year old of age were done to 30 subjects (36.6%). There was a good outcome of the oral health, functional well-being, social emotional well-being, school environment and self image in primary repair cleft lip and palate with the mean overall Child Oral Health Impact Profile (COHIP) score of 102.2. There were significant differences of the overall COHIP and the oral health well-being, school environment and treatment expectation subscales score between the consultants, specialists and trainee. There was no significant difference of overall COHIP and all the subscales score between early and late timing of surgery. Conclusions: Results showed the overall satisfaction post primary cleft lip and palate repair was satisfactory and thus supported the continuation of current management protocol in HKL for the management of cleft lip and palate patients.